High‐pressure sintering of ultrafine‐grained high‐entropy diboride ceramics. Issue 12 (12th August 2020) - Ma, Mengdong; Ye, Beilin; Han, Yangjie; Sun, Lei; He, Julong; Chu, Yanhui
Abstract: Herein the ultrafine‐grained (Hf0.2 Zr0.2 Ta0.2 Nb0.2 Ti0.2 )B2 high‐entropy diboride ceramics were successfully fabricated by high‐pressure sintering technology for the first time. The results showed that the grain size, relative density, and Vickers hardness of the as‐fabricated samples all increased gradually with increasing sintering temperatures from 1373 K to 1973 K. The relative density and mean grain size of the as‐sintered samples at 1973 K were 97.2% and 684 nm, respectively, and simultaneously they exhibited excellent comprehensive mechanical properties, combining a Vickers hardness of 26.2 GPa and a fracture toughness of 5.3 MPa·m 1/2, which were primary attributed to the fine grain strengthening mechanism and microcrack deflection toughening mechanism.